Evaluation of Corporate Strategy and Dynamic Capability to Business Performance (International Journal of Scientific Research and Management (IJSRM), 2018)
A dynamic business environment can affect a company’s business sustainability. This condition will create a competition that must be faced by the business. On the basis of this, the business must be able to apply the right company strategy to realize the dynamic capabilities so that will be able to survive in the global competition and achieve the expected performance. This paper will examine the concepts of strategies undertaken by businesses on the realization of dynamic capabilities and improve overall business performance.